Site‐specific proteolytic degradation of IgG monoclonal antibodies expressed in tobacco plants. Issue 2 (4th October 2014) - Hehle, Verena K.; Lombardi, Raffaele; van Dolleweerd, Craig J.; Paul, Mathew J.; Di Micco, Patrizio; Morea, Veronica; Benvenuto, Eugenio; Donini, Marcello; Ma, Julian K‐C.
Summary Plants are promising hosts for the production of monoclonal antibodies (mAbs). However, proteolytic degradation of antibodies produced both in stable transgenic plants and using transient expression systems is still a major issue for efficient high‐yield recombinant protein accumulation. In this work, we have performed a detailed study of the degradation profiles of two human IgG1 mAbs produced in plants: an anti‐HIV mAb 2G12 and a tumour‐targeting mAb H10. Even though they use different light chains (κ and λ, respectively), the fragmentation pattern of both antibodies was similar. The majority of Ig fragments result from proteolytic degradation, but there are only a limited number of plant proteolytic cleavage events in the immunoglobulin light and heavy chains. All of the cleavage sites identified were in the proximity of interdomain regions and occurred at each interdomain site, with the exception of the VL/CL interface in mAb H10 λ light chain. Cleavage site sequences were analysed, and residue patterns characteristic of proteolytic enzymes substrates were identified. The results of this work help to define common degradation events in plant‐produced mAbs and raise the possibility of predicting antibody degradation patterns 'a priori' and designing novel stabilization strategies by site‐specific mutagenesis.